Waste rice husk ash derived sol: A potential binder in high alumina refractory castables as a replacement of hydraulic binder - Hossain S.S.; Roy P.K. (My University, 2025)
This work provides a new source of binder system, i.e., waste rice husk ash (RHA) derived sol for unshaped refractories. A facile (alkali extraction) route is used to synthesize the sol from the waste RHA. The sol consists of single phase amorphous silica with average particle size around 22 nm. The estimated cost of 30 wt% solid containing RHA derived sol per litre is around 9.35 $. The temperature of mullite (3Al2O3·2SiO2) formation from waste derived sol and reactive alumina containing system is 1250 °C or higher. The sol (30 wt% SiO2) and the dry sol (99.32 wt% SiO2) is used to formulate the high alumina castable samples. The sintering is performed at 1400 °C, 1500 °C and 1550 °C. The different physico-mechanical characterizations and blast furnace slag (BFS) corrosion test at 1500 °C are comprehensively investigated with the prepared castables. The properties of 5 wt% silica (3 wt% from sol and 2 wt% dry sol) containing castable specimens are also equated with the commercially available different silica containing high alumina castable systems. The obtain results are good agreements with the source data. These promising characteristic confirms the possibility of using waste RHA derived sol for manufacturing of cement free high alumina castable and leads to the economic and ecological benefits in the refractory industries. © 2019 Elsevier B.V.